Results of the implementation of social assistance policies for ethnic minority migrant families in Lai Chau province - Phuoc, Dao Mai; Hong, Dong Thi; Giang, Le Huong (Journal of Education, Linguistics, Literature, and Art, 2023)
The Fifth Central Executive Committee Meeting of the Eleventh Tenure on Several Social Policy Issues for the Period 2012 – 2020 claimed that “For many years, our Party and State have always paid attention to constructing and organizing the implementation of social policies, considering them not only objective but also driving forces for sustainable development and stable political and social conditions”. The view point at the conference emphasized that “Ensuring social security is a regular and mandatory task of the Party, the State, the entire political system, and society as a whole.”, especially for the ethnic minorities migrating from poor and disadvantaged areas. The article discusses the results of implementing social assistance policies for ethnic minority migrant families in Lai Chau province. The content of the article reflects that Lai Chau has an undeveloped economy, with outdated customs still prevailing, and many ethnic minority households continue to face difficulties. The reasons for migration among ethnic minority people are primarily due to a lack of farming land and challenging living conditions, leading to migration with family members